Pendampingan Intensif Dan Evaluasi Dampak Penggunaan Teknologi Akuntansi Digital Untuk Penguatan Kapasitas Keuangan UMKM - Kurniawan, Kurniawan (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a strategic pillar of the Indonesian economy, but face serious challenges in financial management, especially in preparing quality financial reports. Many MSMEs in Mojokerto do not understand the importance of accounting for strategic decisions and still use error-prone manual methods. This condition hinders growth and access to financing. In response to these problems, community service program in the form of intensive mentoring on the use of digital accounting technology was implemented. This activity aims to improve the knowledge and skills of MSMEs in Mojokerto in managing finances efficiently and effectively. The activity method uses a pragmatic approach involving lectures, discussions, and hands-on practice with mentoring and coaching methods. Impact evaluation was conducted using a pre-test and post-test design on 10 participating MSMEs. The evaluation results showed a very significant impact: the participants' ability to prepare financial reports increased from 30% before the training to 85% afterwards. 75% of participants found the training very useful, 70% had a better understanding of basic accounting principles, and 65% were more confident in making financial decisions. It was concluded that intensive mentoring based on digital technology is effective in strengthening the financial capacity of MSMEs. A sustainable follow-up program is recommended for long-term program.